2018
DOI: 10.3389/fimmu.2018.01575
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Long-Lived Responses Induced by Immunostimulants and Their Effects on a Viral Infection in Zebrafish (Danio rerio)

Abstract: In recent years, the innate immune response has gained importance since evidence indicates that after an adequate priming protocol, it is possible to obtain some prolonged and enhanced immune responses. Nevertheless, several factors, such as the timing and method of administration of the immunostimulants, must be carefully considered. An inappropriate protocol can transform the treatments into a double-edged sword for the teleost immune system, resulting in a stressful and immunosuppressive state. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 79 publications
1
29
0
Order By: Relevance
“…The nonspecific protection provided by BCG injection also suggests that in fish in vivo evidence for trained immunity already exists. In addition, zebrafish i.p.-injected with b-glucans and subsequently challenged with spring viremia of carp virus (SVCV) either showed a significant but minor increase in survival at seven but not 35 d posttreatment (12) or a clear increase in survival at 14 d posttreatment (41). Thus, relatively long-lived effects of immune stimulants not specifically associated with antiviral immunity provide at least circumstantial in vivo evidence for trained immunity in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonspecific protection provided by BCG injection also suggests that in fish in vivo evidence for trained immunity already exists. In addition, zebrafish i.p.-injected with b-glucans and subsequently challenged with spring viremia of carp virus (SVCV) either showed a significant but minor increase in survival at seven but not 35 d posttreatment (12) or a clear increase in survival at 14 d posttreatment (41). Thus, relatively long-lived effects of immune stimulants not specifically associated with antiviral immunity provide at least circumstantial in vivo evidence for trained immunity in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the conservation of aspects of trained immunity in fish, including the aspects described above. Two recent studies in zebrafish have touched upon such aspects, including observations on an increased antiviral state in rag 2/2 zebrafish associated with increased transcription of innate immune genes (11), and a study describing the lack of effects of pre-exposure to different pathogen-associated molecular patterns on subsequent viral challenges (12). Given the evolutionary position of teleost fish as early vertebrates with a fully developed immune system (13), it is likely that the innate immune cells of fish, such as macrophages, should possess the ability to express specific features of trained immunity.…”
mentioning
confidence: 99%
“…As in other cyprinids, SVCV has been shown to cause severe disease in zebrafish [ 33 ]. Different infection models with SVCV were applied to zebrafish larvae, and important mortalities were reached both by microinjection into the duct of Cuvier [ 34 , 35 , 36 ] and by bath challenge [ 37 , 38 ]. For this, we used both infection routes to analyze the mortality caused by the virus in WT, ptena −/− , and ptenb −/− larvae.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the period of administration, some studies have proposed that the longer administration may cause an overstimulation or a distress generated by the high energy cost due to prolonged exposure to β-glucan [ 21 , 167 , 168 , 169 ]. However, none of the studies that compared periods of β-glucan administration [ 149 , 153 , 170 , 171 , 172 , 173 , 174 , 175 ] found evidence that longer administration periods (up to 56 days) negatively impact the immune system.…”
Section: Routes Of β-Glucan Administrationmentioning
confidence: 99%
“…The studies that reported a negative effect used a high dietary inclusion level (e.g., >0.1%) or injected fish. These treatment protocols may have led to an exacerbated/toxic amount of β-glucan [ 163 , 167 , 174 , 176 ]. Taken together, these findings indicate that longer administrations periods (i.e., >4 weeks) can be beneficial at a low dose, reinforcing the hypothesis suggested by Ai, Mai, Zhang, Tan, Zhang, Xu and Li [ 163 ], Douxfils, Fierro-Castro, Mandiki, Emile, Tort and Kestemont [ 174 ], and Do Huu, Sang and Thanh Thuy [ 175 ] that immunosuppression may be caused by high dose.…”
Section: Routes Of β-Glucan Administrationmentioning
confidence: 99%